Examining spousal and family support as predictors of long-term weight loss and remission of type 2 diabetes following bariatric surgery in Singapore: a retrospective cohort study - Jean C J Liu; Kwang Wei Tham; Edina Yi-Qin Tan; Phong Ching Lee; Sonali Ganguly; Chin Hong Lim (BMJ Open, 2023)
Objectives Postoperative outcomes vary considerably across bariatric patients and may be related to psychosocial factors. In this study, we examined whether a patient’s family support predicts postsurgical weight loss and the remission of type 2 diabetes mellitus (T2DM).Design Retrospective cohort study in Singapore.Setting Participants were recruited from a public hospital in Singapore.Participants Between 2008 and 2018, 359 patients completed a presurgical questionnaire before undergoing gastric bypass or sleeve gastrectomy.Outcome measures As part of the questionnaire, patients described their family support in terms of structure (marital status, number of family members in the household) and function (marriage satisfaction, family emotional support, family practical support). Linear mixed-effects and Cox proportional-hazard models were used to examine whether these family support variables predicted percent total weight loss or T2DM remission up to 5 years postsurgery. T2DM remission was defined as glycated haemoglobin (HbA1c) <6.0% without medications.Results Participants had a mean preoperative body mass index of 42.6±7.7 kg/m2 and HbA1c (%) of 6.82±1.67. Marital satisfaction was found to be a significant predictor of postsurgical weight trajectories. Namely, patients who reported higher marital satisfaction were more likely to sustain weight loss than patients who reported lower marital satisfaction (β=0.92, SE=0.37, p=0.02). Family support did not significantly predict T2DM remission.Conclusions Given the link between marital support and long-term weight outcomes, providers could consider asking patients about their spousal relationships during presurgical counselling.Trial registration number NCT04303611.